2017
DOI: 10.1080/20961790.2017.1287155
|View full text |Cite
|
Sign up to set email alerts
|

Violent offences of methamphetamine users and dilemmas of forensic psychiatric assessment

Abstract: Methamphetamine (MA), an extremely addictive synthetic stimulant, has quickly spread to become the most frequently used illicit drug in China. People with a history of chronic and heavy MA use have a high possibility of exhibiting schizophrenia-like psychotic symptoms, mainly delusions of reference, auditory hallucinations and cognitive deficits. These emerging findings suggest MA use increases aggression and violence and that there is a correlation between MA use and violence. However, it is unclear how to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…Unfortunately, the forensic literature that outlines the relationship between methamphetamine abuse and aggression [4][5][6][7]14,22,32], with its emphasis on pathology and harm, does not trace the causal relationships of biphasic dosing to behaviour. Forensic research is usually correlational, although reliant on neuropharmacological mechanisms developed from animal studies, and from the methodologies such as positron emission tomography to study human brains [11,30].…”
Section: Biochemistry and Neurotransmissionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, the forensic literature that outlines the relationship between methamphetamine abuse and aggression [4][5][6][7]14,22,32], with its emphasis on pathology and harm, does not trace the causal relationships of biphasic dosing to behaviour. Forensic research is usually correlational, although reliant on neuropharmacological mechanisms developed from animal studies, and from the methodologies such as positron emission tomography to study human brains [11,30].…”
Section: Biochemistry and Neurotransmissionmentioning
confidence: 99%
“…Forensic research infers causation from the molecular mechanisms, and pharmacokinetics developed in experimental animal studies and from in-vitro methodologies. Coroners' toxicology data, forensic assessment, and post-mortem assessment of dopamine brain markers [30] are also useful to map onto experimental pharmacology research [4][5][6][7]. Nonetheless, forensic explanatory models for aggression typically correctly identify misuse of drug, and high-dose, mood-induced changes, psychoses, or withdrawal-related aggression in their explanatory bases [11- 23] sectors are emphasized in the international response, with criminal industry a serious problem for societies, policy strategy and law enforcement.…”
Section: Biochemistry and Neurotransmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…While SG has been marketed for the treatment of PD and the metabolites R‐MA and R‐AM are sold over the counter as a nasal inhaler decongestant product, its enantiomers S‐MA and S‐AM are controlled illicit drugs . The difference is mainly because the S‐form has a psychotonic activity 5‐fold stronger than the R‐form . It has been reported that the way to differentiate clinical SG use from MA abuse is chiral analysis of MA and AM in biological specimens, including oral fluid (OF) specimens …”
Section: Introductionmentioning
confidence: 99%
“…5,6 The difference is mainly because the S-form has a psychotonic activity 5-fold stronger than the R-form. [7][8][9] It has been reported that the way to differentiate clinical SG use from MA abuse is chiral analysis of MA and AM in biological specimens, including oral fluid (OF) specimens. 6,8,10,11 OF has been successfully used as an alternative matrix for blood testing in several pharmacokinetic studies and pharmacotoxicological studies.…”
mentioning
confidence: 99%